Understanding of Gold Investment Among Muslim Professionals in Terengganu, Malaysia - Nadhirah, Nordin; Rahimah, Embong; Kasimah, Kamaruddin (Mediterranean Centre of Social and Educational Research, 2015)
Gold investment is a good alternative to maintain financial stability, especially during the global economic turn-down and uncertainties. This becomes a common phenomenon among Muslims today due to the availability of its multiple products, techniques, marketing plans in the current market. Many Muslim investors are eager to get involved in the gold investment, however, some of them do not realize about there are certain products, techniques and marketing plan which are not invalid from a legal standpoint. Therefore, this study was carried out in order to explore about the basic understanding of gold investment among Muslim professional investors. This is a field study that employed the quantitative method where data were obtained through questionnaires. The respondents comprised 300 Muslim professionals from three selected higher institutions which are located in Kuala Terengganu namely Universiti Sultan Zainal Abidin (UniSZA), Universiti Malaysia Terengganu (UMT) and Universiti Teknologi MARA (UiTM). The result of linear regression analysis indicated that, seven significant predictor variables were contributing factor to the level of knowledge about basic gold investment among Muslim professionals in Kuala Terengganu. This suggests that, nul hypothesis were rejected and it could be concluded in general, the seven predictor variables were contributing about 73.9 per cent (r = 0.859) changes of variance in the level of their knowledge about basic investment gold. While a total of 26.1 percent change in variance was influenced by other variables which do not contribute to this analysis.